Influence Of Riparian Vegetation On The Kansas River Flood Of 1993: An Assessment Of Streambank Erosion, Deposition, And Channel Migration - Neppl, Thomas G. (Kansas State University, 1996)
This study explores the influence of woody riparian vegetation on the 1993 Kansas River flood. The extent of streambank erosion, deposition, and channel migration was compared between three landcover and five channel position classifications. Landcover was classified as forest land. non-forest land, and non-forest mix. Channel position was classified as straight, inside curve. outside curve, inside apex. and outside apex. Researchers used 1992 and 1993 aerial slide photographs as the media for investigating the effects of the flood between landcover and channel position classifications. Photocopy reproductions of the slides were digitized and classified with LandCADD"' Rl2 computer-aided design program LandCADD"' was used to organize, illustrate, and present the data. Data analysis was performed using a two-way analysis of variance with a 3 x 5 factorial design. The greatest erosion occurred on non-forested streambanks, the least amount of erosion occurred on forested streambanks. Erosion on non-forest mix streambanks was less than non-forested streambanks and greater than forested streambanks. Findings of erosion attributable to channel position and interactions between channel position and landcover were not significant but demonstrated observed trends. Results suggest that vegetation significantly affected the extent of streambank erosion caused by the 1993 flood. The lack of significant findings for the influence of channel position on streambank erosion shows that the flood was so large it caused extensive erosion at all channel positions. Investigation into the influence of riparian vegetation and channel position on erosion in smaller floods may be needed to provide significant results for both variables.